The athlete's heart. Historical perspectives--solved and unsolved problems - Rost, R. (Cardiology Clinics, 1997)
Clinicians are coming back to Henschen's assessment of the athlete's heart as a physiologic and positive phenomenon. An athlete's heart may be affected by clinical conditions. Regarding the extreme performance of the athlete's heart in training and competition, conditions that may be harmless in sedentary people can be fatal for the athlete. The athlete's heart therefore deserves the particular interest and care of the sports cardiologist.